It Implements in Meetings, Incentives, Conferences, and Exhibitions (Mice) Industry: A Systematic Mapping Study - Afifah Shalihah (International Journal Labs, 2024)
The In this study, we delved into the intersection of digital technology and the MICE sector through a systematic analysis of research literature. Using AI-driven research databases such as Scopus, Emerald, and Consensus, we meticulously curated a corpus of articles to investigate trends and insights. We found that the industry exhibited resilience and adaptability, evident in crisis management strategies and sustainability initiatives. Our curated selection of recommended articles offers actionable insights for practitioners and academics, spanning topics from crisis management to sustainability integration. Moreover, comparative studies across different geographic regions and cultural contexts could shed light on variations in digital adoption and best practices, facilitating cross-cultural learning and knowledge exchange. Finally, interdisciplinary collaborations between researchers, industry practitioners, and policymakers could foster innovative solutions and drive sustainable growth in the industry.